Impact of green human resource management on organizational reputation and attractiveness: The mediated-moderated model - Merlin, Matumona Lubabu; Chen, Yinfei (Frontiers in Environmental Science, 2022)
Globally, there is an increasing concern for environmental sustainability, and the firms are monitored by different stakeholders (i.e., customers, government, suppliers, and current and expected employees). Therefore, this research aimed to explore the impacts of green human resource management (GHRM) on organizational reputation (OR) and organizational attractiveness (OA). The conceptual model of the study is derived from the social identity theory. A close-ended questionnaire was administered to collect data through a web-based survey link shared with 331 employees working in the Democratic Republic of Congo hospitality organization. A partial least square structural equation modeling approach was employed for running data analysis through SmartPLS 3.0 software. The findings of the study reflect that all of the hypotheses were supported. In particular, GHRM has a strong influence on both (OR and OA). While among the OR, green culture and personal environmental orientation, personal environmental orientation strongly affects OA. In addition, OR positively and significantly mediated the relationship between GHRM and OA. Personal environmental orientation significantly moderated the link between GHRM and OA. At the same time, we could not find support for the positive moderation of green culture on the connection between GHRM and OA. This study enhanced the scope of the social identity theory by proposing that OA can be improved by the GHRM, OR, green culture, and personal environmental orientation. In addition, this research suggests that managers in the hospitality sector must include green practices, promote green behavior and initiative, and increase environmental awareness so that employees feel pride in being part of the organization and are attracted to it.